Role of low dose Magnesium sulphate in eclampsia - Sinha, Kajal; K. Sinha, Shail (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Eclampsia is one of the challenging medical complications seen during pregnancy. With the use of magnesium sulphate for control of convulsion in eclampsia, it can be managed effectively. Methods: This is a prospective study done in a tertiary care hospital. Considering low body mass index of patients of developing area, authors had used low dose regime of magnesium sulphate. 100 patients had been enrolled for low dose magnesium sulphate regime after categorizing patients as per inclusion and exclusion criteria. The primary outcome to be measured was recurrence of fits in any patients who received low dose magnesium sulphate. The secondary outcome measured were development of any toxicity, level of serum magnesium level, maternal and perinatal outcome. Results: It was observed that 93% of the patients responded to low dose regime. 7% developed recurrence of fits for that additional dose of 2 gram of 20% magnesium sulphate was given to the patients. Not even a single patient developed signs of toxicity. 94% and 95% of the patients acquired therapeutic level of serum magnesium at 4 hours and 10 hours of magnesium sulphate administration, respectively. Maternal mortality was 5% and perinatal mortality was 24.4%. Conclusions: Low dose of magnesium sulphate can prevent and treat eclampsia. Low dose regimen also reduces incidence of toxicity with improved maternal and perinatal outcome.